Merging the occurrence possibility into gene co-expression network deciphers the importance of exogenous 2-oxoglutarate in improving the growth of rice seedlings under thiocyanate stress - Feng, Yu-Xi; Yang, Li; Lin, Yu-Juan; Song, Ying; Yu, Xiao-Zhang (Frontiers in Plant Science, 2023)
Thiocyanate (SCN−) can find it way to enter cultivated fields, might hamper the harmony in carbon and nitrogen metabolism (CNM) of plants, ebbing their quality and productivity. In the current study, we investigated the role of exogenous application of 2-OG on maintaining homeostasis of CNM in rice seedlings under SCN− stress. Results showed that SCN− exposure significantly repressed the gene expression and activities of CNM related enzymes (e.g., phosphoenolpyruvate carboxylase, NADP-dependent isocitrate dehydrogenases, isocitrate dehydrogenases) in rice seedlings, thereby reducing the relative growth rate (RGR). Exogenous application of 2-OG effectively mitigated the toxic effects of SCN− on rice seedlings, judged by the aforementioned parameters. The co-expression network analysis showed that genes activated in CNM pathways were categorized into four modules (module 1-4). In order to identify the key module activated in CNM in rice seedlings exposed to SCN−, the results from RT-qPCR tests were used to calculate the possibility of occurrence of genes grouped in four different modules. Notably, module 3 showed the highest occurrence probability, which is mainly related to N metabolism and 2-OG synthesis. It is to conclude that exogenous application of 2-OG can modify the imbalance of CNM caused by SCN− exposure through regulating N metabolism and 2-OG synthesis in rice seedlings.